Impaired mitochondria and intracellular calcium transients in the salivary glands of obese rats - Jitjiroj Ittichaicharoen (2018)
© 2017, Canadian Science Publishing. All rights reserved. Long-term consumption of a high-fat diet (HFD) causes not only obese-insulin resistance, but is also associated with mitochondrial dysfunction in several organs. However, the effect of obese-insulin resistance on salivary glands has not been investigated. We hypothesized that obese-insulin resistance induced by HFD impaired salivary gland function by reducing salivation, increasing inflammation, and fibrosis, as well as impairing mitochondrial function and calcium transient signaling. Male Wistar rats (200–220 g) were fed either a ND or an HFD (n = 8/group) for 16 weeks. At the end of week 16, salivary flow rates, metabolic parameters, and plasma oxidative stress were determined. Rats were then sacrificed and submandibular glands were removed to determine inflammation, fibrosis, apoptosis, mitochondrial function and dynamics, and intracellular calcium transient signaling. Long-term consumption of an HFD caused obese-insulin resistance and increased oxidative stress, fibrosis, inflammation, and apoptosis in the salivary glands. In addition, impaired mitochondrial function, as indicated by increased mitochondrial reactive oxygen species, mitochondrial membrane depolarization, and mitochondrial swelling in salivary glands and impaired intracellular calcium regulation, as indicated by a reduced intracellular calcium transient rising rate, decay rates, and amplitude of salivary acinar cells, were observed in HFD-fed rats. However, salivary flow rate and level of aquaporin 5 protein were not different between both groups. Although HFD consumption did not affect salivation, it caused obese-insulin resistance, leading to pathophysiological alteration of salivary glands, including impaired intracellular calcium transients, increased oxidative stress and inflammation, and salivary mitochondrial dysfunction.